2011
DOI: 10.3928/01477447-20110526-08
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Pressure and Related Autonomic Function During Cervical Traction in Healthy Women

Abstract: Cervical traction is a physical therapy procedure frequently used to treat cervical disk lesions, cervical spondylosis, and cervical facet joint lesions. We have observed rare cases of side effects in elderly patients, but not in women younger than 30 years.In this pilot study, 96 young women were randomly divided into 3 groups to study the effect of cervical traction with different traction weights on blood pressure, heart rate, heart rate variability, and correlated autonomic adjustment. Cervical traction we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Similar number of participants were included in a pilot study in which 96 young women were voluntarily involved and had shown effect of cervical traction with different weights on the blood pressure, heart rate, heart rate variability and correlated autonomic adjustment. 10 In another pilot study, 100 healthy young people were included to investigate the responses in cardiovascular functions during cervical traction. 16 However, in our study, BMI was also assessed and was found 23.2 ± 4.1m/kg 2 for group A, 23.1 ± 3.4m/kg 2 in group B and 22.1 ± 4.5m/kg 2 group C. The BMI from the present study was higher compared to another study in which BMI was found for group A was 20.0±2.7, group B 19.5±2.1 and Group C 19.8±3.0.…”
Section: Discussionmentioning
confidence: 99%
“…Similar number of participants were included in a pilot study in which 96 young women were voluntarily involved and had shown effect of cervical traction with different weights on the blood pressure, heart rate, heart rate variability and correlated autonomic adjustment. 10 In another pilot study, 100 healthy young people were included to investigate the responses in cardiovascular functions during cervical traction. 16 However, in our study, BMI was also assessed and was found 23.2 ± 4.1m/kg 2 for group A, 23.1 ± 3.4m/kg 2 in group B and 22.1 ± 4.5m/kg 2 group C. The BMI from the present study was higher compared to another study in which BMI was found for group A was 20.0±2.7, group B 19.5±2.1 and Group C 19.8±3.0.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who are subjected to the therapy are frequently asked to relax, which often leads to their falling asleep [11,23]. It is difficult here to agree with the methodology recommending performing the traction in a sitting position, in which the very act of maintaining the body's upright position requires appropriate muscle tone [12,18,19]. The position suggested in the research performed was inspired, among others, by the fact that while resting, a lot of people adopt the position in which the hands are placed under the head.…”
Section: Discussionmentioning
confidence: 99%
“…Among the procedures used in the therapy of spinal pain syndromes, one of the most frequently recommended is cervical traction [11]. Thanks to a deloading of the spine, and as a consequence, the relaxing of the tensed paravertebral structures, the decompression of the irritated nerve roots as well as improvement in the circulation within the vertebral artery, and as a consequence, increased statokinetic efficiency, occur [12,13]. The methods of performing the traction are varied (Peake 2005, Myśliwiec 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Raney et al [53] used traction forces of 23.2lbs (103 N), Young et al [46] used 35lbs (156 N), Fater and Kernozek [38] used 13.6 Kg (133 N), Tsai et al [54] used 10%–30% of body weight (47 N–141 N), and Forbush et al [45] used traction forces of 9–13 kg (88 N–128 N). Young et al used 5lbs (22 N) as a sham traction force for their control group [46].…”
Section: Discussionmentioning
confidence: 99%